Fluorodeoxyglucose positron emission tomography–computed tomography in a pregnant woman with carcinoma breast - Mahato, Abhishek; Joshi, Richa; Harish, S; Paliwal, Dharmesh (World Journal of Nuclear Medicine, 2021)
A 35-year-old female with a 15-week period of gestation was detected with locally advanced cancer of the left breast. She was suggested to undergo a medical termination of pregnancy (MTP) followed by invasive Oncological imaging - Contrast enhanced computed tomography (CECT) chest–abdomen–pelvis/fluorodeoxyglucose positron emission tomography-CT (FDG PET-CT) for staging the disease. However, to avoid the risk of iatrogenic novel coronavirus 2019 infection to the patient, on her request, the hospital admission was carried out after the oncological workup and thus PET-CT was conducted before the MTP. FDG PET-CT revealed FDG avid primary in the left breast along with extensive metastases to liver and skeletal lesions. The developing fetus also showed physiological FDG uptake. The patient has undergone an MTP and is presently under treatment for metastatic breast cancer. The case report illustrates the radiation safety guidelines on fetal radiation exposure, steps to decrease fetal radiation exposure, and illustration of fetal FDG uptake.
Keywords: Breast cancer; fetal fluorodeoxyglucose; pregnancy